Race, nation, history : Anglo-German thought in the Victorian era - Steinberg, Oded Y. (Oded Yair), 1980- (Intellectual history of the modern age., 2019)
Oded Y. Steinberg argues that historical periodization converged with racial, national, and religious themes to inform the historical perception of influential English and German scholars during the second half of the nineteenth century.